The Role of Campus Sports Facilities in Increasing Student Motivation to Exercise - Hudain, Muh. Adnan (ILIN Education Indonesia, 2025)
This research aims to analyze the role of campus sports facilities in increasing student motivation to exercise at the Faculty of Sports Science and Health (FIKK) Universitas Negeri Makassar (UNM). Sports facilities are one of the important components in supporting students' physical activities in the campus environment. This research uses a quantitative approach with a survey method on 150 FIKK UNM students selected through purposive sampling. The research instrument uses a questionnaire that has been tested for validity and reliability to measure the quality of sports facilities and the level of student motivation to exercise. Data were analyzed using descriptive analysis and simple linear regression analysis. The research results show that campus sports facilities have a significant influence on student motivation to exercise with a coefficient of determination (R²) value of 0.682 or 68.2%. Adequate, well-maintained, and easily accessible facilities have been proven to increase students' intrinsic and extrinsic motivation to engage in regular sports activities. This research concludes that improving the quality and accessibility of campus sports facilities can be an effective strategy in encouraging an active and healthy lifestyle among students.